3D measurement & modelling using close range laser scanner for reverse engineering application - Zainuddin, Khairulazhar; Setan, Halim; Majid, Zulkepli (2008)
Reverse Engineering (RE) is the process of discovering the technological principles of a device, object or system through analysis of its structure, function, and operation. The RE process involves measuring an object and then reconstructing it as a 3D model. The physical object can be measured using 3D scanner like CMM, laser scanner, structured light digitizer and computed tomography. This study focuses on the technique and method of measuring and modeling 3D object using Konica Minolta Vivid 910 close range laser scanner and RapidForm2004 software. Vivid 910 is powerful tool for scanning 3D objects and RapidForm2004 is standard software for processing the point cloud into 3D model. In this study, Eurocopter 350Z Prototype Helicopter Model data have been captured using close range laser scanner and been processed using RapidForm2004. There are several stages in processing point cloud including point-processing and polygon optimization. The result 3D model was exported into RE formats i.e. STL, IGES and STEP for RE downstream applications using RE software. In summary, the laser scanner technology offer wide potential applications in 3D measurement and modeling.